2020
DOI: 10.1080/02687038.2020.1759268
|View full text |Cite
|
Sign up to set email alerts
|

Behind the therapy door: what is “usual care” aphasia therapy in acute stroke management?

Abstract: Background: Usual care is the term used to describe everyday practice in the management of a client within a profession. The knowledge of the tasks used in therapy and key therapeutic processes used within these treatments, provides critical information about if and how the therapy works. The Very Early Rehabilitation in SpEech Randomised Controlled Trial (VERSE RCT) had three arms with therapists within the intensive Usual Care-Plus arm (UC-Plus) providing daily direct aphasia therapy at their discretion for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 58 publications
(97 reference statements)
1
8
0
Order By: Relevance
“…7 Our current findings were unexpected, based on our pilot studies 5,18 which showed significant benefit of early, intensive aphasia treatment. In addition, we found a considerable increase in the amount of aphasia therapy provided as usual care, but not in the type of therapy provided, 37 compared with the results of our pilot trial. 5 Our Phase I trial 5 was conducted over 10 years ago, and at this time, among the 15% of participants who received aphasia therapy, only 14 min was provided in a single session over three weeks.…”
Section: Discussionsupporting
confidence: 48%
“…7 Our current findings were unexpected, based on our pilot studies 5,18 which showed significant benefit of early, intensive aphasia treatment. In addition, we found a considerable increase in the amount of aphasia therapy provided as usual care, but not in the type of therapy provided, 37 compared with the results of our pilot trial. 5 Our Phase I trial 5 was conducted over 10 years ago, and at this time, among the 15% of participants who received aphasia therapy, only 14 min was provided in a single session over three weeks.…”
Section: Discussionsupporting
confidence: 48%
“…• Duration of practice reflected by time spent in a therapy space [20][21][22] or time on task, 5,23 for example, minutes/hours; • Schedule of therapy, for example, frequency of sessions, days/week [24][25][26] ; • Task difficulty, for example, challenge point 27 ; or • Physical intensity, for example, Borg rating scale, 28 heart rate reserve, 29 metabolic equivalent of task, 29 or repetitions. 5 The breadth and diversity of unidimensional approaches to articulate dose suggest there is a global lack of agreement.…”
Section: Challenge 2: Dose Is Multidimensionalmentioning
confidence: 99%
“…Further, the treatment fidelity reported here was completed at the macrostructure level. Previously published work [22,23] presents finer grained, utterance level analyses and adds nuanced therapeutic information to the efficacy picture. Finally, the receipt of treatment and enactment of treatment skills areas of Bellg et al [5] were not measured in this study and so cannot be commented on.…”
Section: Study Limitationsmentioning
confidence: 99%